Cultural Memory and Identity Politics: An Ethnographic Study of Manuscript Preservation Practices at Sanggar Surya Pringga Dermayu, Indramayu - ute lies khadijah; elnovani lusiana; agus rusmana; rully khairul anwar (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2026)
Using six months of participant observation (2024) and in-depth interviews with 15 community members, this research reveals three key findings. First, manuscripts are understood as animate entities with ancestral agency, requiring ritual care rather than technical conservation alone. Second, preservation activities—including transliteration workshops and ritual readings—function as cultural performances where community members actively negotiate contested meanings of "tradition," "authenticity," and "modernity." Third, significant power asymmetries based on gender and generation shape access to manuscript knowledge, with elder men monopolizing textual expertise while women and youth employ subtle forms of resistance. The study demonstrates how manuscripts function as "living archives"—sites of active cultural production rather than passive storage. In post-Suharto Indonesia, manuscript preservation serves as regional identity politics, as the sanggar uses Javanese-script texts to assert Javanese identity against Sundanese cultural hegemony. However, the sanggar faces severe structural constraints—financial precarity, institutional marginalization, and succession crisis—that threaten long-term sustainability. This study contributes to Indonesian anthropology by theorizing community heritage practices as dynamic identity formation processes embedded in power relations and neoliberal governance, where communities bear preservation responsibility without corresponding state support.